Scabies in the Elderly: A Narrative Literature Review - Aurelia Stella Stephanie; Aurelia Stephanie (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Scabies is an ectoparasite infestation of the skin caused by the mite Sarcoptes scabiei. In diagnosing scabies in the elderly, the practitioner should consider the overall clinical picture, including history, physical examination, and diagnostic tools to assist in making clinical decisions. In this population, early diagnosis and treatment of scabies are essential to prevent secondary infection and sepsis. Treatments that can be given to scabies in the elderly include eradication of mites, treatment of symptoms and complications, and therapy in close contact to prevent transmission. This literature review aims to discuss the pathophysiology, diagnosis, and management of scabies in the elderly.